Exercise and Nutritional Supplements' Role in Reducing Traumatic Brain Injury in American Football - Kyle Rank; Giovanna Ramos; Cameron Addie; Tyler Neltner; Mike Fraser; Ludmila M. Cosio-Lima; Christopher Wirth; Debra Vinci; Youngil Lee (Sports and Exercise Medicine, 2024)
Given the prevalence of traumatic brain injuries (TBI) in contact sports such as American Football, the need for increased research in TBI has been dramatically increased over the last 20-years. TBI has two main mechanisms that cause neuronal cell death following an incident: direct axonal death and neuronal inflammation, with the latter being the most common because it persists more than a decade and chronically affects neighboring neurons. Therefore, proper management that reduces inflammation post-TBI should be stressed in order to facilitate propitious recovery. While sideline concussion protocols have been implemented in sports fields, it is important immediately to initiate recovery protocols in order to minimize the degree of progressive neuronal death caused by TBI. While difficult to individualize symptoms for each occurrence, it is essential to incorporate a pretest of cognition, memory, and balance as a means of determining the severity of TBI. Although the sports concussion assessment tool 2 has been used by collegiate and professional teams, this tool is just based on observation and comparison. Thus, more precise and advanced diagnosis using biological methods are needed to accurately assess individual symptoms, which should save lives. One example is to use serum creatine kinase (CK) levels because CK released from damaged brain tissues enters the bloodstream and thus TBI can be quickly assessed and identified. While the immediate diagnosis of TBI is one part of management, efficacious treatments of post-TBI is also critical. Regarding this, exercise and nutritional supplementation have been reported to be effective. While specific pathways of neuroprotective mechanisms remain to be elucidated, endurance exercise along with supplementation of fish oil, caffeine, and vitamin D seems to elicit neuroprotective effects. This review provides potential mechanisms responsible for exercise and nutritional supplementation-mediated neuroprotection against TBI. Since human subjects are limited to mechanistic studies requiring invasive surgical procedures, research involving animals (e.g., mouse and rat) are also introduced in this review.